Skin's green autofluorescence at dorsal centremetacarpus may become a novel biomarker for diagnosis of lung cancer. Issue 5 (14th February 2022) - Zhang, Mingchao; Tao, Yue; Chang, Qing; Wang, Kaixuan; Chu, Tianqing; Ying, Weihai
Abstract: It is critical to discover novel biomarkers of lung cancer for establishing economical technology for diagnosis of lung cancer. Our study has suggested that the autofluorescence (AF) of the skin may become a novel biomarker of this type: First, development of lung cancer led to a significant increase in the skin's green AF in a mouse model of lung cancer; second, lung cancer patients had significantly higher skin's green AF at certain positions compared with healthy volunteers and pulmonary infection patients; and third, using the skin's green AF intensity at dorsal centremetacarpus as the variable, the areas under curve (AUC) for differentiating lung cancer patients and pulmonary infection patients and for differentiating lung cancer patients and healthy volunteers was 0.871 and 0.813, respectively. Collectively, our study has indicated that the skin's green AF at dorsal centremetacarpus may become a novel biomarker for establishing a ground‐breaking diagnostic strategy for lung cancer. Abstract : It is highly valuable to discover novel biomarkers of lung cancer for establishing economical and non‐invasive diagnostic technology for the disease. Our study has indicated that the skin's green AF at dorsal centremetacarpus may become a biomarker for establishing a ground‐breaking diagnostic strategy for lung cancer: Using the AF as variable, the areas under curve (AUC) for differentiating lung cancer patients and pulmonary infection patients and for differentiating lung cancer patients and healthy volunteers was 0.871 and 0.813, respectively.